KEBIJAKAN REDAKSI MEDIA SOSIAL PARTAI DEMOKRASI INDONESIA PERJUANGAN JAKARTA TIMUR DALAM MENENTUKAN PEMBERITAAN - Bayquni, Bayquni (Universitas Prof. Dr. Moestopo (Beragama), 2019)
In this study, researchers tried to research a social media that people might not know much about, namely the Facebook Fan Page Account Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Jakarta Timur. The purpose of this study is to find out more in the editorial policies of Facebook Fan Page Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Jakarta Timur in determining the news worthy of circulation. In order to study more about social media editorial policies Facebook Fan Page Account Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Jakarta Timur Jakarta Timur researchers use the methodology of Moderate Participation Observation: in this study there is a balance between researchers being insiders and being outsiders. The researcher also participated in participatory observation in several activities, but not fully. The results of this study are Facebook Fan Page Accounts Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Jakarta Timur Jakarta Timurhave a policy in making news. News writers are required to have a mindset that is in accordance with the style of language and writing must also be in accordance with the segmentation of the reader, in order to understand what they need to observe how to advance the theory of Hierarchy of Influence in Facebook Fan Page Accounts Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Jakarta Timur.